Projeto de prevenção primária e secundária de doenças cardiovasculares da FCT/UNESP de Presidente Prudente - Torquato, Paula Rapchan dos Santos [UNESP] (2015)
Introduction: The cardiovascular disease have a significant increase along the years, increasing the number of deaths related with thispatology. Your appearance is relate with a number of risk factors that direct the prevention programs, searching the health benefits of the participants. Objective: Describe the activity developed on the Primary and Second Cardiovascular Disease Prevention Project of Attendance and Studies Center in Physical Therapy and Rehabilitation (FCT/UNESP) and characterize the individuals participants of this project on 2015. Materials and methods: The project is develop with patients of Attendance and Studies Center in Physical Therapy and Rehabilitation (FCT/UNESP/PresidentePrudente) doing preventive cardiovascular risk factors activities like obesity, blood pressure, diabetes, dyslipidemia, sedentarism, smoking and stress. These activities involving questionnaires application, preventive activities, and evaluation. To characterize the sample we utilized descriptive statistical. Results and Discussion: There is on the project participants higher prevalence of seniors, individuals classified as overweight with the BMI, and moderate to high risk on waist-to-rip ratio. The project development have been promoting benefits effects on the life style of the participant population, and, contributing professionally and personally to the project integrant studies. Conclusion: The primary and secondary prevention program have fundamental importance, addressing the cardiovascular disease risk factors, and how to modify then, and contributes with de integral formation of the project participants studies.